Pathology of Calcineurin and Mammalian Target of Rapamycin Inhibitors in Kidney Transplantation - Leal, Rita (Kidney Int Rep, 2017)
The recent evolution in immunosuppression therapy has led to significant improvement in short-term kidney allograft outcomes; however, this progress did not translate into similar improvement in long-term graft survival. The latter, at least in part, is likely to be attributed to immunosuppressant side effects. In this review, we focus on the histologic manifestations of calcineurin inhibitor and mammalian target of rapamycin inhibitor toxicity. We discuss the pathologic features attributed to such toxicity and allude to the lack of highly specific pathognomonic lesions. Finally, we highlight the importance of clinicopathologic correlation to achieve a meaningful pathologic interpretation.